2012
DOI: 10.5402/2012/828626
|View full text |Cite
|
Sign up to set email alerts
|

Caval Aorta Index and Central Venous Pressure Correlation in Assessing Fluid Status! “Ultrasound Bridging the Gap”

Abstract: Accurate body fluid assessment and estimation of fluid status are essential in guiding fluid therapy in emergency setup. This prospective cross-sectional descriptive study conducted to ascertain the effectiveness of inferior vena cava and aorta (IVC/Aorta) index in assessing the fluid status by comparing it with the central venous pressure (CVP). Results showed the mean IVC/Aorta index in patients who had normal CVP range was 1.2 ± 0.12 SD, while in patients with low CVP, the mean index was 0.7 ± 0.09 SD, and,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 14 publications
0
19
0
3
Order By: Relevance
“…10 This could be due to that the inferior vena cava (IVC) is a highly compliant vessel with no valves and its size varies with changes in intra vascular pressure, blood volume, right heart function and the degree of collapsibility during the respiratory cycle predicts the fluid status of the patient. 7,11,12 A study conducted by Ozdemir et al, in children with nephrotic syndrome found that there was no significant difference between the nephrotic syndrome patients (0.66±0.33) and controls (0.60±0.3) for IVCI (P >0.05). 13 The values for the IVCCI in the nephrotic patients (39.4±8.6) were much lower than the values calculated for the control subjects (56.9±8.7) (P <0.05).…”
Section: Resultsmentioning
confidence: 95%
“…10 This could be due to that the inferior vena cava (IVC) is a highly compliant vessel with no valves and its size varies with changes in intra vascular pressure, blood volume, right heart function and the degree of collapsibility during the respiratory cycle predicts the fluid status of the patient. 7,11,12 A study conducted by Ozdemir et al, in children with nephrotic syndrome found that there was no significant difference between the nephrotic syndrome patients (0.66±0.33) and controls (0.60±0.3) for IVCI (P >0.05). 13 The values for the IVCCI in the nephrotic patients (39.4±8.6) were much lower than the values calculated for the control subjects (56.9±8.7) (P <0.05).…”
Section: Resultsmentioning
confidence: 95%
“…In 1979, Natori et al . for the first time proved the correlation between the alterations in IVC diameter and right atrial blood pressure ( 15 ) . At present, the measurement of the inferior vena cava (IVC) and inferior vena cava collapsibility (IVCCI) are effectively used to determine the body fluid status of dialysis patients ( 14 , 16 ) .…”
Section: Discussionmentioning
confidence: 97%
“…The conducted studies demonstrated a significant correlation between weight and diameter of the aorta both in transverse and longitudinal views (correlation coefficient >0.7). The literature suggests that the measurements of the index may be used interchangeably with CVP which is currently considered the most accurate method in assessing the fluid status of patients ( 15 ) . The non-invasive character of sonography suggests its greater usefulness in daily clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A modality which may offer the possibility of even more accurate assessment of the fluid status and enable monitoring of patients is sonography ( 4 , 5 ) . The ultrasound assessment of the diameter of the inferior vena cava and aorta (IVC/Ao index) with the ultrasound transducer placed in the anterior median line is a recognized method ( 6 , 7 ) used in the emergency departments and intensive care units. The limitations of this method include: trauma in the substernal region, wound dressing or substantial amount of gas in the intestines.…”
Section: Introductionmentioning
confidence: 99%